Effective enhancement of Pseudomonas stutzeri D-phenylglycine aminotransferase functional expression in Pichia pastoris by co-expressing Escherichia coli GroEL-GroES - Kanidtha Jariyachawalid (2018)
Background: D-phenylglycine aminotransferase (D-PhgAT) of Pseudomonas stutzeri ST-201 catalyzes the reversible stereo-inverting transamination potentially useful in the application for synthesis of D-phenylglycine and D-4-hydroxyphenylglycine using L-glutamate as a low cost amino donor substrate in one single step. The enzyme is a relatively hydrophobic homodimeric intracellular protein difficult to express in the soluble functionally active form. Over-expression of the dpgA gene in E. coli resulted in the majority of the D-PhgAT aggregated into insoluble inclusion bodies that failed to be re-natured. Expression in Pichia pastoris was explored as an alternative route for high level production of the D-PhgAT.Results: Intracellular expression of the codon-optimized synthetic dpgA gene under the P AOX1 promoter in P. pastoris resulted in inactive D-PhgAT associated with insoluble cellular fraction and very low level of D-PhgAT activity in the soluble fraction. Manipulation of culture conditions such as addition of sorbitol to induce intracellular accumulation of osmolytes, addition of benzyl alcohol to induce chaperone expression, or lowering incubation temperature to slow down protein expression and folding rates all failed to increase the active D-PhgAT yield. Co-expression of E. coli chaperonins GroEL-GroES with the D-PhgAT dramatically improved the soluble active enzyme production. Increasing gene dosage of both the dpgA and those of the chaperones further increased functional D-PhgAT yield up to 14400-fold higher than when the dpgA was expressed alone. Optimization of cultivation condition further increased D-PhgAT activity yield from the best co-expressing strain by 1.2-fold.Conclusions: This is the first report on the use of bacterial chaperones co-expressions to enhance functional intracellular expression of bacterial enzyme in P. pastoris. Only two bacterial chaperone genes groEL and groES were sufficient for dramatic enhancement of functionally active D-PhgAT expression in this yeast. With the optimized gene dosage and chaperone combinations, P. pastoris can be attractive for intracellular expression of bacterial proteins since it can grow to a very high cell density which is translated into the higher volumetric product yield than the E. coli or other bacterial systems. © 2012 Jariyachawalid et al.; licensee BioMed Central Ltd.